(untitled) (Latakia University Journal -Basic Sciences Series, 2016)
في هذا البحث ندرس دالة غاما وتمثيلها لمتحول عقدي، وذلك باستخدام إما سلسلة أو تكامل مناسب وتطبيقاتها في حل بعض أنواع المعادلات التكاملية وعلاقتها بدالة زيتا لريمان، واستخدامها في حل التكامل المحيطي، وفي إيجاد تكامل هانكل المحيطي وفقاً لدالة بيسل من أجل عدد صحيح n. In this paper, we study the Gamma function, and the representation of a complex variable, using either sequential or appropriate integration ,and its application in solving certain types of integral equations , and their relationship to the Riemann- Zeta function, and used to solve the contour integration ,and to find the integration of Hankel’s contour integral according to Bessel function for integer n.